Community Characteristics, Victimization, and Psychological Adjustment Among School-Aged Adopted Children With Lesbian, Gay, and Heterosexual Parents - Goldberg, Abbie E.; Garcia, Randi (Frontiers in Psychology, 2020)
Little research has examined victimization among school-aged children raised in lesbian/gay (LG) parent households and almost no work has attended to the school and community contexts that may impact their victimization risk. This study examined predictors of parent-reported child victimization and child adjustment, and parent responses to victimization, in 43 two-mother, 37 two-father, and 56 mother–father families, with adopted children (median age = 8.6 years). Predictors included parent (sexual orientation), school (climate, public versus private) and community (urbanicity, percentage voted Democrat) factors, with parent and child demographics included as controls. A total of 47% of parents reported one or more child victimization experiences in the past year; there were no differences by family type. An exploratory interaction between family type and urbanicity indicated that in large urban areas, children with LG parents were predicted to experience less victimization than children with heterosexual parents; in more rural regions, children with LG parents were predicted to experience more victimization than children with heterosexual parents. School climate was related to victimization: Parents who reported more negative school climate reported more child victimization. Children with higher levels of parent-reported victimization had higher levels of parent-reported internalizing and externalizing symptoms. In large urban areas, children with LG parents were predicted to have fewer internalizing symptoms than children with heterosexual parents; in more rural areas, children with LG parents were predicted to have more internalizing symptoms than children with heterosexual parents. Regarding parents’ responses to victimization, LG parents were more likely to talk to school administrators, their children, and the bully, compared to heterosexual parents.